Divulgação de informações voluntárias em relatórios financeiros e seu relacionamento com a estrutura das empresas e características dos contabilistas - Beuren, Ilse Maria (1991)
There are three main objectives in this study: firstly, to evaluable the level of voluntary disclosure in annual financial reports by listed industrial corporations, as well as to demonstrate this level’s evolution over time; secondly, to verify the relation between the level of disclosure and the size of the companies on the one hand, and accountants professional satisfaction and their interest in innovating their work on the hand; finally, to examine the connection between the frequency of voluntary disclosure and the relative importance given by the financial analysts and accountants responsible for two annual reports to the items of information. In order to achieve these purposes, tree of Almeida’s (1988) hypotheses have been contested, and, as an extension of the research, another three hypotheses have been formulated to explain variations in the level of voluntary disclosure. The data necessary to test the hypotheses were obtained in two ways. To evaluate the level of voluntary disclosure the financial reports of 1987 were requested in the Santa Catarina State from twenty six chosen for this purpose industrial companies whose shares are available at the Stock Exchange. To establish the level of professional satisfaction and interest in innovating the accountants were submitted to a structured interview. Pearson’s correlation coefficient was applied in the analysis. The results showed a low level of disclosure as well as its slight increase in 1987 compared to the period of 1984-86. The correlation coefficients analysis determined a link between the level of voluntary disclosure and the size of companies, as well as the accountants interest in innovations. A positive relation between the frequency of the items of information divulged and their relative importance declared by accountants and financial analysts was evidenced in this study, too.